2019
DOI: 10.21203/rs.2.10930/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development, Validation and Translation of Cardiopulmonary Resuscitation and Automated External Defibrillator Training and Placement Bilingual Questionnaire

Abstract: Objectives: The paper describes the development and translation of a questionnaire purported to measure (1) the perception of the placement strategy of automated external defibrillator, (2) the perception on the importance of bystander cardiopulmonary resuscitation and automated external defibrillator (3) the perception on the confidence and willingness to apply these two lifesaving interventions as well as (4) the fears and concerns in applying these two interventions.For construct validation, iterative runs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The reliability and validity were tested using four different methods: the factor loading, Cronbach's alpha, composite reliability, and average variance extracted (AVE). According to Chew et al (2019), the values of the variables in factor loading found to be less than 0.7 should be avoided unless they are essential for validity contents. Thus, the threshold value was determined as 0.6.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The reliability and validity were tested using four different methods: the factor loading, Cronbach's alpha, composite reliability, and average variance extracted (AVE). According to Chew et al (2019), the values of the variables in factor loading found to be less than 0.7 should be avoided unless they are essential for validity contents. Thus, the threshold value was determined as 0.6.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The difficulty of the KOR-AED items varied, with certain items showing a medium level of difficulty, especially the questions related to the use of the AED and others a higher discriminatory index, In addition, Cronbach's alpha of 0.75 indicates an acceptable internal consistency of the KOR-AED test, however other studies of development and validation of questionnaires in CPR and AED use showed a Cronbach's alpha of 0.84 (11) and 0.9 (12) attributable to social contexts and familiarity with the use of the AED other than our own.…”
Section: Discussionmentioning
confidence: 96%